Presencia de lo judío en la poesía argentina contemporánea - Geneviève Fabry (Cuadernos LIRICO)
This article is composed of the analysis of a corpus of 21st century poetry collections published by Argentinian female authors born around the 1950s and embracing their Jewish inheritance in their stories: Tamara Kamenszain’s El ghetto (2003), Mercedes Roffé’s Canto errante y Memorial de agravios (2002) and Liliana Lukin’s Ética demostrada según el orden poético (2011). What is at stake is to be able to determine which facets of the Jewish identity this poetry embodies : either religious, cultural or sensible ones ? In these collections under study, the act of writing through the remembrance of a cultural and religious Jewish inheritance is repeated so as to invite oneself to embrace and to reflect upon these lyrical topics.